Kandungan Bakteri Patogen Dalam air Cucian Dan Profil Pembeli Makanan Minuman Pedagang Kaki Lima di Kotamadya Yogyakarta tahun 1999 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Food Comsumption in Yogyakarta is a very important aspect that need to be studied carefully. Firstly, Yogyakarta is a lourisme City and Secondly, Yogyakarta is an education city where there are many students are learning. Therefore, here food consumption and food consumer are necessary to be studied very deeply. The result of this research shows that the quality of providers habit in preparing food is quite low, for instance the use of contamination water and therefore the number of E. coil and other microbiologyâ Parameters are quite high.